2021
DOI: 10.3390/nu13030759
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Role of Food and Dietary Modifications in Patients with Inflammatory Bowel Disease: Impact on Lifestyle

Abstract: Background: Diet has a relevant role in triggering symptoms in inflammatory bowel disease (IBD) from the patients’ perspective, but there is gap the between patients’ and doctors’ perceptions. Few studies have addressed this topic. The aim of this study was to evaluate food habits and nutrition knowledge in a homogeneous cohort of patients with IBD from southern Italy. Methods: 167 consecutive patients with IBD were recruited. The survey was based on the administration of a semi-structured questionnaire assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Similar research from New Zealand revealed that 55% of patients with CD complained of exacerbation of symptoms after beer consumption. Similarly, in the recent study of Guida et al, almost 19% of patients perceived alcohol as a symptoms trigger [ 75 ].…”
Section: Alcoholmentioning
confidence: 82%
“…Similar research from New Zealand revealed that 55% of patients with CD complained of exacerbation of symptoms after beer consumption. Similarly, in the recent study of Guida et al, almost 19% of patients perceived alcohol as a symptoms trigger [ 75 ].…”
Section: Alcoholmentioning
confidence: 82%
“…Some studies have found that patients are also likely to follow an ‘unguided’ diet (meaning no guidance from a physician or dietitian), where daily dietary choices are based on patients’ perceptions of foods or on the experiences of others 18,19 . Knowledge from professionals may not be comprehensive and detailed enough, and patients will form the basis for their own dietary decisions after receiving expertise and combining it with their own dietary experience 20 . One participant described their decision‐making around dietary choices as ‘changing the foods I naturally eat, without even thinking about it, and then becoming more aware.’ This process can also be described as perceptual eating 17 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Knowledge from professionals may not be comprehensive and detailed enough, and patients will form the basis for their own dietary decisions after receiving expertise and combining it with their own dietary experience. 20 One participant described their decisionmaking around dietary choices as 'changing the foods I naturally eat, without even thinking about it, and then becoming more aware. '…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the environmental factors, diet might play a relevant role. Furthermore, patients with IBD often have the perception that food can worsen their disease, and their excessive focus on the quality, quantity, and type of food that they intake can lead to unhealthy habits and, in some cases, caloric–protein malnutrition [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%